Mengembangkan Kecerdasan Logika Matematika Anak Melalui Media Celemek Hitung Pada Kelompok B Di TK Pertiwi Sidowarno II Wonosari Klaten Tahun Ajaran 2014-2015 - Apriliyani, Dwi, Dr. Darsinah, M. Si (2015)
The aims scrip of this reseacrh was to develop logical mathematic intelligence for group B on TK Pertiwi Sidowarno II Sidowarno Subdistict Wonosari Regency Klaten Academic Year 2014-2015 through Arithmetic Apron. The research was a classroom action research (CAR). The subject of this research was students of group B, 5-6 years old, on TK Pertiwi Sidowarno II Sidowarno Subdistict Wonosari Regency Klaten academic year 2014-2015. The research was held in two cycles. Each cycle consisted of two meetings. The data was collected by observation and field record. Analysis technical was used comparative analysis, critical analysis and one way anova. Before cycle the result of child reaching expected development (RED) 35,71%. Cycle I was 71,43%, and cycle II was 92,86%. Based on F test the result of arithmetic F was bigger than F table or 11,426 ≥ 3,24, so that Ho was rejected and Ha was accepted. It mean that there was the significant differences on the result of development. The was conclusion if this research was that through arithmetic apron if could develop the logical mathematic intelligence for group B on TK Pertiwi Sidowarno II Wonosari Klaten academic year 2014-2015.